Assessment of foods for infants and toddlers in Australia against the World Health Organization's Nutrient and Promotion Profile Model for food products for infants and young children - Alexandra Chung; Sophia Torkel; Judith Myers; Helen Skouteris (Cambridge University Press, 2024)
Abstract Objective: Global public health agencies have recommended stronger regulation of food marketing to protect children's diets. This study assessed commercial foods for infants and toddlers available in Australian supermarkets for compliance with the World Health Organization (WHO) Regional Office for Europe's Nutrient and Promotion Profile Model: supporting appropriate promotion of food products for infants and young children 6-36 months in the WHO European Region (NPPM). Design: Dietitians assessed a sample of commercial foods for infants and toddlers against the composition, labelling and promotion requirements of the NPPM. Setting: Australia. Participants: Commercial foods for infants and toddlers (n 45) available in two major Australian supermarkets, purposely sampled across product categories and brands. Results: Fewer than one quarter (23 %) of the assessed products met all nutrient content requirements of the NPPM. No products met all of the labelling or promotional requirements. All products included at least one promotional marketing claim that was not permitted under the NPPM. Conclusions: The NPPM is useful to assess and monitor the nutritional composition and prevalence of marketing claims on commercial foods for infants and toddlers. Findings of noncompliance with the NPPM recommendations indicate an urgent need for stronger government regulation of the composition, labelling and marketing of commercial foods for infants and toddlers in Australia.